(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Currently, new changes and additions to education are being made in secondary special and general education schools. The main content and essence of this is to improve the quality of education in schools. Every year, several reforms are carried out to control the quality of education in schools. The main purpose of this is to form rating indicators in schools. Providing high-quality education to students is the main task of a teacher in this school. This requires high knowledge and pedagogical skills from the teacher. When developing educational programs in schools, the teacher uses several methods of delivering information on the subject to students and chooses the most effective method. For example, the teacher should determine the level of the student’s knowledge by presenting the necessary information on the subject through slides, pictures or interesting information. This article provides information on the creation of methods related to the topic of developing the pedagogical skills of teachers.